“Asyraf & Adab 5” Android 3D animation application - Ahmad Latfi, Noor Maizatul Ain; Tahir, Nur Amirah; Abd Malik, Sofianiza (2014)
Akademi Fakih Intelek (AFI) together with Quranic Research Centre, University of Malaya (UM) is an organization exists to help disabled children to learn Al-Quran as well as the acts of worship (Ibadah) in Islam. Children under these categories learn through visual, auditory and kinesthetic. Instead of applying the common and conventional method of teaching to these children particularly involving the Quran, and Ibadah learning, the administrators decided to try different kind of approach; using multimedia as the medium of communication and education. This approach gained positive feedback from the teachers, parents and as well as the children themselves. Therefore the animators decided to be part of this great project to contribute in the children’s development.